Prevalence and circumstances of forced sex and post-migration HIV acquisition in sub-Saharan African migrant women in France : an analysis of the ANRS-PARCOURS retrospective population-based study - (:unkn) unknown (My University, 2018)
Background : Sub-Saharan African migrant women are a key population at risk of HIV infection in Europe. Using data from the ANRS-PARCOURS study, we aimed to assess the prevalence of forced sex after migration and its association with post-migration acquisition of HIV as well as the circumstances of forced sex after migration, including housing and administrative insecurity, among sub-Saharan African migrant women living in the Paris Region, France. Methods The ANRS-PARCOURS study was a retrospective life-event survey done between February, 2012, and May, 2013, in health-care facilities in the Paris region of France. Women were eligible if they were born in sub-Saharan Africa, aged between 18 and 59 years, and had been diagnosed with HIV infection at least 3 months earlier for women receiving HIV care or not diagnosed with HIV. In this analysis, we used ANRS-PARCOURS study data to compare the incidence of forced sex after migration in three groups of sub-Saharan African migrant women: those who acquired HIV after migrating, those who acquired HIV before migrating, and those without HIV. We assessed the associations between forced sex, sexual partnerships, and living conditions after migration with mixed-effects logistic regression and generalised structural equation models. The study is registered with ClinicalTrials.gov, number NCT02566148. Findings We obtained data from 980 eligible individuals who participated in the ANRS-PARCOURS study (407 without HIV and 573 HIV-positive) from 54 randomly selected health-care facilities. We excluded 20 women whose HIV infection could not be dated and eight women with missing data from the analyses, for a total of 405 women in the reference group (without HIV) and 547 women in the HIV group (156 with post-migration HIV acquisition, 391 with pre-migration HIV). Women who acquired HIV after migration experienced forced sex after migration more frequently than women without HIV (24 [15%] vs 18 [4%]; p=0.001). Forced s
Keywords: African Research